SISTEM PENJADWALAN UJIAN DENGAN METODE ITERATIVE FORWARD SEARCH (STUDI KASUS: FTI UNTAR) - Fransisca Regina; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
An exam application is made using Iterative Forward Search  algorithm. FTI Untar is used as a study case in this application development The purpose of using this algorithm is to get a schedule that not break constraints.  The results of the tests done for the courses scheduling of odd semester of 2012 / 2013, even semester of 2012 / 2013 , odd  semester of 2013 / 2014, and odd  semester of 2014 / 2015,  there is no hard-constraints (constraints that must be satisfied) violation, no soft-constraint violation, and no students who need to participate in more than one exam at the same time. It is also concluded the subject is not scheduled, because students of subject is more than maximum’s capacity of room’s exam. The other result is the existing schedule is not yet considering  of maximum’s exam of students every day.  Key wordsExamination Timetabling, Iterative Forward Search (IFS), Inisialisation solution, Exam, University Examination Timetabling Problem